2020
DOI: 10.1002/ijc.32965
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐specificity phosphatase 6 plays a critical role in the maintenance of a cancer stem‐like cell phenotype in human endometrial cancer

Abstract: The prognosis of patients with high‐grade or advanced‐stage endometrial cancer remains poor. As cancer stem‐like cells (CSCs) are thought to be associated with endometrial cancers, it is essential to investigate the molecular mechanisms that regulate endometrial CSCs. Dual‐specificity phosphatase 6 (DUSP6) functions as a negative‐feedback regulator of MAPK–ERK1/2 signaling, but its role in endometrial cancer remains unknown. We investigated whether DUSP6 is involved in cancer cell stemness using endometrial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For A3B, endogenous peroxidases were blocked using 3% hydrogen peroxide in methyl alcohol for 15 min. The slides were incubated with a primary antibody at 4°C overnight and with a secondary antibody at room temperature for 1 h. The IHC signal was detected using DAB (Wako), and the nuclei were stained with hematoxylin as we have described previously [ 14 ]. In each case, the total IHC score was calculated by at least 2 examiners using a BZ-X710 microscope (Keyence).…”
Section: Methodsmentioning
confidence: 99%
“…For A3B, endogenous peroxidases were blocked using 3% hydrogen peroxide in methyl alcohol for 15 min. The slides were incubated with a primary antibody at 4°C overnight and with a secondary antibody at room temperature for 1 h. The IHC signal was detected using DAB (Wako), and the nuclei were stained with hematoxylin as we have described previously [ 14 ]. In each case, the total IHC score was calculated by at least 2 examiners using a BZ-X710 microscope (Keyence).…”
Section: Methodsmentioning
confidence: 99%
“…Among OCT4 isoforms, OCT4B1 and OCT4A serve important roles in apoptosis ( 25 , 31 , 33 ). Therefore, we hypothesized that OCT4B1 and OCT4A rather than other OCT4 isoforms may mediate the apoptosis induced by PHF20 knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has demonstrated that PHF20 is involved in tumorigenesis ( 25 ). However, the expression level and role of PHF20 in apoptosis and cisplatin sensitivity remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…DUSP4 is considered a candidate tumour suppressor gene, and its deletion is related to the occurrence of breast cancer, rectal cancer, thyroid cancer and other tumours 17,18 . DUSP6 is expressed at low levels in the tumour tissues of many human malignancies, including ovarian cancer and endometrial cancer 19,20 .…”
Section: Discussionmentioning
confidence: 99%